Incidental Prostate-Specific Membrane Antigen Uptake in a Peripheral Nerve Sheath Tumor. (July 2017) - Vamadevan, Shankar; Le, Ken; Shen, Lily; Ha, Leo; Mansberg, Robert
Abstract : Abstract: A 66-year-old man with recently diagnosed prostate cancer (Gleason score 9) was referred for 68 Ga–prostate-specific membrane antigen (PSMA) PET/CT with prostate-specific antigen level of 7.5 μg/L. PET/CT demonstrated increased PSMA uptake (SUVmax 4.7) in a soft tissue density in the left adductor compartment. MRI and cytopathology of the biopsied soft tissue density was compatible with a peripheral nerve sheath tumor. This case illustrates that PSMA uptake can occur in a peripheral nerve sheath tumor and should be taken into consideration as a benign cause of PSMA uptake.